Formulation of Blush On Cream from Hibiscus Sabdariffa (L.) Flower Extract - Tubagus Akmal; Yenni P. Tanjung; Yudhea Afrizki (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Natural dyes have become more popular as a result of the harmful and carcinogenic effects of syntheticdyes. Anthocyanins are natural dyes that are widely used to replace synthetic dyes and can also act asantioxidants that can be found in rosella (Hibiscus sabdarrifa L.). This study aimed to obtain blushon cream from rosella flower extract (RFE) with olive oil and to determine the effect of olive oilconcentration on the evaluation results. The blush on cream was made in 3 formula, F1 (13,5%),F2 (15,5%), and F3 (17,5%). The cream was evaluated for 28 days in room temperature (15–30⁰C)which included organoleptic, pH, homogeneity, spreadability, adhesion, cream type, and viscosity.The results of the evaluation of RFE blush on cream with olive oil showed that F1, F2, and F3 metthe requirements for evaluating the preparation for organoleptic tests, pH, homogeneity, spreadability,adhesion, cream type, and viscosity. Variations concentration of olive oil gave no significant effect(p>0,05) on the organoleptic, pH, homogeneity, spreadability, and cream type and had significant effect(p<0,05) on the adhesion and viscosity test. The findings demonstrate that RFE can be made in blushon cream formulations with olive oil as emollients.